Increasing Mocaf-based Businesses in West JAVA - R. Oktini, Dede; Dwi Nugraha, Yudha; Roosalyn, Allya; Rahmi, Dewi (KnE Social Sciences, 2023)
The problem of small entrepreneurs lies in the drying of cassava chips. Incomplete drying causes the color to become black, the taste and aroma to be less than perfect. The drying technique used was sunlight, because during the rainy season the production cannot be continued with limited stock and increased number of orders, while stock is limited and orders increase. This program is directed to an apprenticeship with the aim to make oven in the future. Another problem is the need to expand. Therefore, training on making mocaf noodles was held because the market for noodles was high. The market will be wider through product/derivative diversification, which has implications for increasing people’s income and welfare. Another activity is involving participants in online marketing training. The purpose of PKM is to increase and maintain production continuity and increase profits through the creation of derivative products. The target audience were people who are already engaged in the mocaf business, small culinary entrepreneurs. The training methods involved tutorials and technical training based on Islamic values. Based on the results of the apprenticeship, small equipment can be easily made; however, the larger ones were not completed due to the shortage of funds. The manufacturing and marketing of noodles have been occupied by a number of small culinary entrepreneurs, and sold to meatball traders and consumers who were customers initially. Keywords: production, diversification, mocaf, noodles